Dosimetria Física e Controle de Qualidade em Radioterapia - Eberlin, Bárbara Büscher von Teschenhausen [UNESP] (2008)
Radiotherapy is a multidisciplinary speciality which uses complex equipment and radiation sources for delivery of treatment, using high-energy ionizing radiation to treat cancer at several stages of complexity. Since radiation therapy is a technique which involves a precalculated radiation dose, it shall be established quality assurance programs that provide an efficient and safety treatment. The International Commission on Radiation Units and Measurements (ICRU) report No. 50 has recommended dose uniformity between 5% of the prescribed dose throughout the region of interest. This is one of the most primordial points that justify the importance of a suitable attendance of the equipments quality and performance. For quality control, the medical physicist will be involved with establishing and running a Quality Control Program (QCP). He must adapt or develop the procedures of equipment acceptance and commissioning, besides verifying the use of principles and accepted protocols of national and international reports to assure the correct quality, quantity, and placement of radiation during the performance of a radiological procedure, establishing adequate protocols to ensure accurate patient dosimetry. This present work consists of a description of the activities carried through the Sectors of Radiation Therapy of the Hospital of Clinics of the Campinas State University (Unicamp), particularly in the implementation of the Quality Control Program